2010
DOI: 10.1002/ppul.21400
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation is no more effective than usual care for the treatment of primary dysphagia in children

Abstract: NMES treatment of anterior neck muscles in a heterogeneous group of pediatric patients with dysphagia did not improve the swallow function more than that seen in patients who did not receive NMES treatment. However, there may be subgroups of children that will improve with NMES treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 19 publications
1
42
0
1
Order By: Relevance
“…33 Neuromuscular electrical stimulation (NMES) Systematic review of evidence showed promising but insufficient evidence with need for high-quality controlled trials; 34 NMES of anterior neck muscles did not improve swallow function more than patients receiving usual oral motor training and dietary manipulations without NMES 35 …”
Section: Oral Appliances or Feeding Devicesmentioning
confidence: 99%
“…33 Neuromuscular electrical stimulation (NMES) Systematic review of evidence showed promising but insufficient evidence with need for high-quality controlled trials; 34 NMES of anterior neck muscles did not improve swallow function more than patients receiving usual oral motor training and dietary manipulations without NMES 35 …”
Section: Oral Appliances or Feeding Devicesmentioning
confidence: 99%
“…One recent study evaluated the use of neuro-motor electrical stimulation (NMES) of anterior neck muscles in a heterogeneous group of children with dysphagia [56]. The authors reported that, overall, NMES treatment did not improve the swallow function more than a control intervention.…”
Section: Management Of Pediatric Swallowing Disordersmentioning
confidence: 99%
“…[39,40,41,42,43,44]). Others [36,45] suggested a negative effect of electric stimulation on hyolaryngeal elevation [46,47] or found no significant differences between traditional therapeutic methods and NMES [48,49,50,51,52,53]. …”
Section: Dysphagiamentioning
confidence: 99%